2019
DOI: 10.1080/08870446.2019.1672873
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of adherence to oral hypoglycaemic agents: an application of the ProMAS questionnaire

Abstract: Objectives: This study aimed to identify psychological predictors of oral hypoglycaemic agent (OHA) adherence and to compare adherence rates between a novel and well-known instrument, i.e. the Probabilistic Medication Adherence Scale (ProMAS) and Medication Adherence Report Scale (MARS-5). Design and main outcome measures: A longitudinal study design was applied with surveys at baseline and 6-month followup. At baseline, OHA adherence using the ProMAS and MARS-5, socio-cognitive determinants and demographics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…We observed that patients with a lower education level described more problems, reported less engagement with DSM, and more passive reliance on primary care professionals than those with higher education qualifications. This is consistent with the previous literature, which shows an association between a lower education level and lower DSM and self-efficacy [21,24,25,42]. Both education and knowledge degree are determinant factors of the attitudes of patients to take pills and follow a healthy lifestyle [30,43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that patients with a lower education level described more problems, reported less engagement with DSM, and more passive reliance on primary care professionals than those with higher education qualifications. This is consistent with the previous literature, which shows an association between a lower education level and lower DSM and self-efficacy [21,24,25,42]. Both education and knowledge degree are determinant factors of the attitudes of patients to take pills and follow a healthy lifestyle [30,43].…”
Section: Discussionsupporting
confidence: 92%
“…The focus groups took place between October 2019 and January 2020. The participants were distributed into four groups (Table 1) according to their age (<65 vs. ≥65 years) and educational level (with university degree vs. with no university degree), as previous research shows that age and education level may be linked to differences in diabetes self-management (DSM), health literacy, and health-related expectations and needs [21][22][23][24][25]. The focus groups lasted approximately 60-75 min and were video-recorded to facilitate voice recognition of the participants if needed.…”
Section: Data Collectionmentioning
confidence: 99%
“…The proportion of patients in this study who were adherent measured by the MARS (90.9%) was approximately the same as the proportion of adherent patients reported in a previous study of diabetes medication (89.5%) where the MARS score of 23 was used as the cut off to categorise patients as adherent [ 37 ]. Overestimation of the adherence rate may, however, result from patient reluctance and unwillingness to disclose their non-adherent behaviour or report not taking medicines as prescribed [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 52%
“…Higher scores represent better adherence levels. In this study, a cut‐off point of 90% [ 37 ] was used and the patients who had total scores ≥ 23 were considered adherent. The total BMQ scores of the necessity scale and the concern scale range from 5 to 25.…”
Section: Methodsmentioning
confidence: 99%
“…8 While the questionnaire has been shown to be reliable in predicting nonadherence across several conditions, 12,14 the current study assesses the validity and reliability of a shorter number of items for clinical utility. Whilst there have been studies utilising a shorter form of MARS, based on an initial validation study in asthma patients by Horne and Weinman 12 these have shown variability in its reported accuracy in various conditions, 15,16 or have focused on validation in other languages or countries. 17,18 The Medication Adherence Report Scale (MARS-5, ©Professor Rob Horne)a shorter form of MARS-10 comprises items which describe a range of nonadherent behaviours, with items phrased in a nonthreatening and nonjudgmental way to normalise nonadherence, and a response scale that allows the categorisation of patients in terms of their position along the "adherence dimension" rather than on the basis of a "yes/no" or "high/low" dichotomous response, thus providing more detail and differentiation between individuals.…”
Section: What This Study Addsmentioning
confidence: 99%